1984
DOI: 10.1007/bf03186303
|View full text |Cite
|
Sign up to set email alerts
|

Histology and histopathology of the feeding lesions byCyrtopeltis tenuis Rent. (Hemiptera: Miridae) onLycopersicon esculentum Mill. (Solanaceae)

Abstract: Aspects of histology and histochemistry of injured tissues of Lycopersicon esculentum Mill due to feeding by the mirid, Cyrtopeltis tenuis Reut, based on increased activities of proteins, tannins, peroxidases, polyphenol oxidases and acid phosphatases are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…() reported that N. tenuis is able to survive for a few days but not to complete its development when feeding on tomato plants alone. In contrast, Raman and Sanjayan () found that N. tenuis was able to complete its development in 18 days – with 100% survivorship – when feeding only on tomato plants. In the present work, only a low proportion of nymphs (0.184–0.229) were able to complete their development when feeding on plants, and the development times were much longer than the values reported by Raman and Sanjayan ().…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…() reported that N. tenuis is able to survive for a few days but not to complete its development when feeding on tomato plants alone. In contrast, Raman and Sanjayan () found that N. tenuis was able to complete its development in 18 days – with 100% survivorship – when feeding only on tomato plants. In the present work, only a low proportion of nymphs (0.184–0.229) were able to complete their development when feeding on plants, and the development times were much longer than the values reported by Raman and Sanjayan ().…”
Section: Discussionmentioning
confidence: 91%
“…This increase in the concentrations of some amino acids below the necrotic rings could be due, among other reasons, to damage at feeding sites resulting in the blockage of the phloem. Nesidiocoris tenuis uses a lacerate‐and‐flush feeding strategy that necroses tissues along the stylet path, resulting in the hypertrophy and hyperplasy of cells surrounding the phloem that produce characteristic necrotic rings at feeding sites (Raman and Sanjayan ; Raman et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the success of these predators has been 496 mainly attributed to their efficient predation of a wide 497 range of important pests Calvo et al 498 2012b;P érez-Hedo and Urbaneja 2014) and to their phy-499 tophagy (Calvo et al 2009), which allows them to become 500 established prior to pest appearance and to maintain their 501 populations in periods of prey scarcity. Remarkably, N. 502 tenuis was formerly considered a tomato pest because of 503 feeding-based damage such as necrotic rings in apical 504 stems (Raman and Sanjayan 1984;Calvo et al 2009) when 505 prey is scarce. However, thanks to proper management 506 (exhaustive monitoring and adoption of corrective mea-507 sures when needed), this predator has shifted from being 508 considered a pest to becoming a key biological control 509 agent for successful pest management (Calvo et al 2012a).…”
mentioning
confidence: 99%
“…560 rejection is that heavily B. tabaci-infested tomato plants 561 could induce a plant response similar to that caused by N. 562 tenuis, i.e., activation of the ABA pathway, given that both 563 hemipterans have piercing-sucking mouthparts and feed on 564 vascular bundles, particularly phloem tissue and the 565 neighboring parenchyma cells (Raman and Sanjayan 1984;566 Walker 2010). Thus, whiteflies could also identify plants 567 emitting HIPVs triggered by the ABA pathway signaling as 568 plants already highly populated by conspecific whiteflies, 569 which would impair the successful development of their 570 progeny through increased competition.…”
mentioning
confidence: 99%